The Study of Electromagnetic Scattering by a Non-Perfectly Conductor in Chiral Media by Potential Theory (Communications in Mathematical Research, 2021)
This paper is concerned with the electromagnetic scattering by a non-perfectly conductor obstacle in chiral environment. A two-dimensional mathematicalmodel is established. The existence and uniqueness of the problem are discussed bypotential theory.